Total and cause-specific mortality associated with meat intake in a large cohort study in Korea - Kityo, Anthony; Lee, Sang-Ah; Kang, Daehee (Frontiers in Nutrition, 2023)
Background Asia has experienced a large increase in meat intake in the past decade, yet the health impact of meat intake is not well studied. Objective We examined the association of meat intake with all-cause, cancer and cardiovascular disease (CVD) mortality in an Asian country. Methods Participants were 113,568 adults with dietary data at recruitment (2004-2013) of the Health Examinees-Gem (HEXA-G) study, a prospective cohort study conducted in 8 regions of Korea. Participants were followed until 31 December 2020. Total, red, white, and organ meat intake were computed based on a 106-item questionnaire. Multivariable Cox proportional hazard models were implemented using the lowest quintile of meat intake as the reference category. Findings For 1,205,236 person-years, 3454 deaths were recorded. High intake of processed red meat was positively associated with all-cause mortality (men: hazard ratio (HR) 1.21, 95% confidence interval (95% CI) 1.07-1.37; women: HR 1.32, 95% CI 1.12-1.56). Increased risk of all-cause mortality (HR 1.21, 95% CI 1.05-1.39) and cancer mortality (HR 1.24, 95% CI 1.03-1.50) was observed in women with high intake of organ meat. Moderate intake of pork belly was associated with reduced risk of all-cause mortality in men (HR 0.76, 95% CI 0.62-0.93) and women (HR 0.83, 95% 0.69-0.98) but high intake was associated with increased risk of CVD mortality in women (HR 1.84, 95% CI 1.20-2.82). Low beef intake decreased the risk of CVD mortality in men (HR 0.58, 95% CI 0.40-0.84), but roasted pork increased cancer mortality in women (HR 1.26, 95% CI 1.05-1.52). Conclusion There was increased risk of all-cause mortality associated with intake of processed red meat in men and women, increased risk of all-cause and cancer mortality with intake of organ meat in women, and increased risk of cancer mortality with intake of roasted pork intake in women. High intake of pork belly increased the risk of CVD mortality in women, but moderate intake was inversely associated with mortality from all-causes in both men and women.